Analysis of Higher Order Thinking Skills (HOTS) Based on Bloom Taxonomy in Comprehensive Examination Questions - Anita Inggrith Tuela; Yolanda Nany Palar (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The study aims to examine the distribution of questions in the Higher Order Thinking Skills (HOTS) category on the comprehensive examination of the Biblical Major at the IAKN Manado Theology Study Program, with the indicator for the Higher Order Thinking Skills (HOTS) questions based on the revised Bloom's Taxonomy. A descriptive method with a qualitative approach was applied. Data which was sourced from the comprehensive examination of Biblical Major at Theology Study Program of IAKN Manado, then analyzed using an interactive analysis model by Miles and Huberman, including data condensation, data display, verification, and conclusion. Analysis of questions was according to the revised Bloom's Taxonomy by Anderson & Krathwohl (2001). The results indicated that the comprehensive examination questions of Biblical majors at the Theology Study Program were taken from 15 courses with a total of 100 questions. Of the 100 questions, it was found that 9 courses contained HOTS questions and 6 courses contained questions classified in the MOTS and LOTS categories. Specifically, the percentages in each cognitive level were as follows, C6 at 1%, C5 at 16%, C4 at 23%, C3 at 38%, C2 at 8% and C1 at 14%. Thus, the HOTs level achieved 40%, the MOTS level reached 38%, while the LOTS level got 22%. It was concluded that the comprehensive examination questions of the Biblical Major at the Theology Study Program of IAKN Manado were dominated by the HOTS questions, although they were not evenly distributed in all questions of the subjects tested. The results of this study can be used as a reference in the preparation of exam questions for all subjects, so that the test administrator team or educators can determine the quality of each question made. Furthermore, the test administrators will also be able to map the categories of questions based on HOTS, MOTS, and LOTS, therefore the exam questions quality can be improved which affects the increase of students' higher-order thinking skills (HOTS).